Analisis Perbandingan Tingkat Kesehatan Bank Menggunakan Metode Risk-Based Bank Rating (RBBR) Studi Pada Bank Milik Pemerintah Pusat Periode 2018-2022 - Bela Septiana; Sri Rahayuningsih (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
This study aims to determine the comparison of the soundness level of Central Government-Owned Banks, namely PT Bank Rakyat Indonesia Tbk, PT Bank Negara Indonesia Tbk, PT Bank Mandiri Tbk, and PT Bank Tabungan Negara Tbk based on the Financial Services Authority Regulation Number 4/POJK.03/2016 concerning the Assessment of Commercial Bank Validity Level using the RBBR (Risk-Based Bank Rating) method. The period used in his research is 5 years, starting from 2018 to 2022. This type of research uses qualitative descriptive research. The data taken is secondary data in the form of the annual financial statements of PT. Bank Rakyat Indonesia Tbk, PT Bank Negara Indonesia Tbk, PT Bank Mandiri Tbk, PT Bank Tabungan Negara Tbk for the 2018-2022 period. This study used an assessment method based on the calculation of each variable. Risk Profile assessment uses Non-Performing Loan (NPL) and Loan to Deposit Ratio (LDR) ratios. Good Corporate Governance uses the results of Self Assessment of GCG implementation that has been published by PT Bank Rakyat Indonesia Tbk, PT Bank Negara Indonesia Tbk, PT Bank Mandiri Tbk, PT Bank Tabungan Negara Tbk. Earning assessment uses the ratio of Return On Asset (ROA) and Net Interest Margin (NIM). Capital uses the Capital Adequacy Ratio (CAR). The results of research and data analysis can be concluded that the bank's soundness level using the RBBR method (Risk-Based Bank Rating) at PT Bank Rakyat Indonesia Tbk and PT Bank Mandiri Tbk during 2018-2022 obtained a Composite Rating 1 (PK-1) in the "Very Healthy" category. Meanwhile, PT Bank Negara Indonesia Tbk and PT Bank Tabungan Negara Tbk during 2018-2022 obtained Composite Rating 2 (PK-2) in the "Healthy" category.